Designing an industrial protocol to develop a new fat-reduced- ice cream formulation by replacing stabilizers with microbial transglutaminase enzyme - Akin, M. Serdar (Array, 2019)
In this study, the possibility of replacing stabilizers with microbial transglutaminase (MTG) enzyme in fat-reduced ice cream production was studied. In addition, the stage of adding (before or after the heat treatment) the MTG enzyme to ice cream was also investigated. Five different ice creams (A and C containing 1 unit MTG/g protein without stabilizer, B and D containing 0.5 unit MTG/g protein and 0.35 % stabilizer, which also consist of the mixture of Carrageenan (E 407), Guar gum (E 412), Xanthan gum (E 415) and Sodium alginate (E 401), and E (control) containing 0.7 % stabilizer) were manufactured. MTG has been added to samples A and B after heat treatment while it was added to C and D samples before the heat treatment. An experimental analysis related to the overrun, viscosity melting properties, pH, titratable acidity, dry matter, fat, protein, sensorial and microstructural properties of ice creams was carried out. According to the results, the amount and the adding stage of MTG significantly affected overrun, melting, viscosity, coldness, firmness, smoothness, mouth coating, color, appearance, taste, smell scores, and also microstructure of ice creams (p<0.01). Results also showed that MTG could be used together with other stabilizers after heat treatment in the production of ice cream. Moreover, our findings demonstrated that sample B was the closest to control in terms of sensorial properties.